Brachial-ankle pulse wave velocity is associated with both acute and chronic cerebral small vessel disease. (February 2016) - Kim, Yong Bum; Park, Kwang-Yeol; Chung, Pil-Wook; Kim, Jeong-Min; Moon, Heui-Soo; Youn, Young Chul
Abstract: Objective: The aim of this study was to determine the association of brachial-ankle pulse wave velocity (baPWV) with both acute and chronic cerebral small vessel disease (SVD). Methods: We identified 1282 consecutive patients with acute ischemic stroke or transient ischemic attack. Neuroimaging correlates of chronic lacunes, white matter hyperintensity (WMH), and cerebral microbleed (CMB) were assessed using MR images. Combined SVD score was defined as the number of presence of SVD markers including chronic lacunes, WMH, deep CMB, and acute lacunar infarction. The association between baPWV and SVD was tested using linear and logistic regression analyses. Results: Mean age of patients was 68 (±12) years. Chronic lacunes were found in 675 patients (53%), WMH in 970 patients (77%), and deep CMB in 349 patients (30%). Among the 1145 patients with ischemic stroke, 292 patients (26%) were classified as having acute SVD. On multivariate analysis, a 1-SD increase in baPWV was associated with chronic lacunes [odds ratio, 1.24; 95% CI, 1.07–1.44; p < 0.01], WMH (1.38; 1.13–1.71; p < 0.01), deep CMB (1.29; 1.11–1.51; p < 0.01), acute SVD (1.19; 1.01–1.40; p = 0.04), combined SVD score >1 (1.27; 1.06–1.53; p = 0.01), and combined SVD score >2 (1.40; 1.19–1.65; p < 0.01). Conclusions: baPWV is associated with both acute and chronic SVD. Our findings suggest that arterial stiffness is linked to the pathogenesis of SVD. Also, baPWV could be used as a biomarker of SVD. In future trials, it should be tested whether arterial stiffness can be a therapeutic target for SVD. Highlights: We investigated the association of arterial stiffness with small vessel disease. Arterial stiffness was measured by ankle-brachial pulse wave velocity. Pulse wave velocity was associated with chronic small vessel disease. Pulse wave velocity was associated with acute small vessel occlusion in the brain. Arterial stiffness may be linked to the pathogenesis of small vessel disease.